XRK3F2 Inhibition of p62-ZZ Domain Signaling Rescues Myeloma-Induced GFI1-Driven Epigenetic Repression of the Runx2 Gene in Pre-osteoblasts to Overcome Differentiation Suppression - Adamik, Juraj; Silbermann, Rebecca; Marino, Silvia; Sun, Quanhong; Anderson, Judith L.; Zhou, Dan; Xie, Xiang-Qun; Roodman, G. David; Galson, Deborah L. (Frontiers in Endocrinology, 2018)
Multiple myeloma bone disease (MMBD) is characterized by non-healing lytic bone lesions that persist even after a patient has achieved a hematologic remission. We previously reported that p62 (sequestosome-1) in bone marrow stromal cells (BMSC) is critical for the formation of MM-induced signaling complexes that mediate OB suppression. Importantly, XRK3F2, an inhibitor of the p62-ZZ domain, blunted MM-induced Runx2 suppression in vitro, and induced new bone formation and remodeling in the presence of tumor in vivo. Additionally, we reported that MM cells induce the formation of repressive chromatin on the Runx2 gene in BMSC via direct binding of the transcriptional repressor GFI1, which recruits the histone modifiers, histone deacetylase 1 (HDAC1) and Enhancer of zeste homologue 2 (EZH2). In this study we investigated the mechanism by which blocking p62-ZZ domain-dependent signaling prevents MM-induced suppression of Runx2 in BMSC. XRK3F2 prevented MM-induced upregulation of Gfi1 and repression of the Runx2 gene when present in MM-preOB co-cultures. We also show that p62-ZZ-domain blocking by XRK3F2 also prevented MM conditioned media and TNF plus IL7-mediated Gfi1 mRNA upregulation and the concomitant Runx2 repression, indicating that XRK3F2’s prevention of p62-ZZ domain signaling within preOB is involved in the response. Chromatin immunoprecipitation (ChIP) analyses revealed that XRK3F2 decreased MM-induced GFI1 occupancy at the Runx2-P1 promoter and prevented recruitment of HDAC1, thus preserving the transcriptionally permissive chromatin mark H3K9ac on Runx2 and allowing osteogenic differentiation. Furthermore, treatment of MM-exposed preOB with XRK3F2 after MM removal decreased GFI1 enrichment at Runx2-P1 and rescued MM-induced suppression of Runx2 mRNA and its downstream osteogenic gene targets together with increased osteogenic differentiation. Further, primary BMSC (hBMSC) from MM patients (MM-hBMSC) had little ability to increase H3K9ac on the Runx2 promoter in osteogenic conditions when compared to hBMSC from healthy donors (HD). XRK3F2 treatment enriched Runx2 gene H3K9ac levels in MM-hBMSC to the level observed in HD-hBMSC, but did not alter HD-hBMSC H3K9ac. Importantly, XRK3F2 treatment of long-term MM-hBMSC cultures rescued osteogenic differentiation and mineralization. Our data show that blocking p62-ZZ domain-dependent signaling with XRK3F2 can reverse epigenetic-based mechanisms of MM-induced Runx2 suppression and promote osteogenic differentiation.